2022
DOI: 10.1186/s13102-022-00480-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of maturation, fitness, and hormonal indices on minutes played in elite youth soccer players: a cross-sectional study

Abstract: Background The main purpose of this study was to investigate the relationships between minutes played (MP) with maturity status, fitness, and hormonal levels, and to quantify their influence on minutes played. Methods Twenty-four elite youth soccer players under-16 years participated in this study, over a full-season period. Anthropometric measures, maturity status, hormonal and physical fitness levels were collected. Participants were monitored du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…However, this is not supported by the negative and moderate correlation found between AW-1 and VO 2max and the absence of a relationship between VO 2max and AW-2. This inverse relationship between the AW-1 and VO 2max can eventually be interpreted by the fatigue accumulated in the first half of the season [ 48 ]. Although there are no significant differences, the AW absolute values in the first half were higher than in the second.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not supported by the negative and moderate correlation found between AW-1 and VO 2max and the absence of a relationship between VO 2max and AW-2. This inverse relationship between the AW-1 and VO 2max can eventually be interpreted by the fatigue accumulated in the first half of the season [ 48 ]. Although there are no significant differences, the AW absolute values in the first half were higher than in the second.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to performance, lower-limb asymmetries (LLA) have frequently been studied to quantify performance differences between limbs [ 9 , 10 , 11 , 12 ] and a bilateral asymmetry in youth [ 1 ]. Madruga-Parera et al [ 13 ] demonstrated that contrast resistance training programs reduced interlimb asymmetries score (−0.70 moderate vs. −0.32, small), more than isoinertial resistance training in youth male handball players.…”
Section: Introductionmentioning
confidence: 99%
“…Coaches seem to perceive those demonstrating high levels of fundamental motor skills as better players. Conversely, other studies indicate that biological maturation, fitness status, and physical dimensions are the discriminant factors involved in the selection, as well as minutes played in elite youth football (soccer) [13,14]. Under those circumstances, estimating how effectively coaches discriminate between players during group formation is complex.…”
Section: Introductionmentioning
confidence: 99%